Human microglia and astrocytes express cGAS-STING viral sensing components. (29th September 2017) - Jeffries, Austin M.; Marriott, Ian
Highlights: Primary and immortalized human microglia and astrocytes are responsive to foreign intracellular double stranded DNA. Human microglia and astrocytes show robust expression of cytosolic DNA sensor, cyclic GMP-AMP synthase (cGAS), at rest and after activation. Human microglia and astrocytes constitutively express the critical downstream cGAS adaptor protein, stimulator of interferon genes (STING). Abstract: While microglia and astrocytes are known to produce key inflammatory and anti-viral mediators following infection with replicative DNA viruses, the mechanisms by which these cell types perceive such threats are poorly understood. Recently, cyclic GMP-AMP synthase (cGAS) has been identified as an important cytosolic sensor for DNA viruses and retroviruses in peripheral leukocytes. Here we confirm the ability of human microglial and astrocytic cell lines and primary human glia to respond to foreign intracellular double stranded DNA. Importantly, we provide the first demonstration that human microglia and astrocytes show robust levels of cGAS protein expression at rest and following activation. Furthermore, we show these cell types also constitutively express the critical downstream cGAS adaptor protein, stimulator of interferon genes (STING). The present finding that human glia express the principle components of the cGAS-STING pathway provides a foundation for future studies to investigate the relative importance of these molecules in clinically relevant viral CNS infections.